ANALISIS MANAJEMEN SUMBER DAYA MANUSIA KESEHATAN (SDMK) DI PUSKESMAS BANGKALAN - Sari Maduratna, Enggal; Firdaus, Nailufar; Laila, Alfa (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2024)
The aim of the research is to analyze the management of Health Human Resources (SDMK) at the Bangkalan Community Health Center by identifying POAC (Planning, Organizing, Actuating, Controlling). The research method is qualitative with a descriptive approach. Data collection techniques use interviews, observation and documentation. The research was conducted at the Bangkalan Health Center in January-February 2024. The key informants are the head of the community health center and the Head of Administration, the main informants are the Personnel Coordinator and the Management Coordinator and the triangulation informants are the Head of the Human Resources Division and the Head of the HR Section of the Bangkalan District Health Service. Based on the research results, it is known that the inequality of HRK is seen in terms of numbers. Where currently there are more health workers at the Bangkalan Community Health Center than midwives. Meanwhile, the health workers who are lacking are nutritionists. From the results of data analysis, it was found that the HRK qualifications at the Bangkalan Community Health Center did not meet the standard specifications in accordance with Minister of Health Regulation number 43 of 2019 concerning Community Health Centers, namely the lack of one health worker needed to support health services. The implementation of HRK management at the Bangkalan Community Health Center has been going well but is still ongoing. not yet optimal, especially in the areas of equality and qualifications that are not yet appropriate. So it is necessary to re-assess according to the qualifications.